How Organizational Commitment, Work Ability and Work Motivation influence Employee Performance in Case of Lurik Weaving MSMEs in Special Region of Yogyakarta? - Lung, Rosalina; Jaidi, Nahiyah; Suryaningtyas, Arum (Journal of Office Administration : Education and Practice, 2025)
This study aims to examine the influence of organizational commitment, work ability, and work motivation on the performance of employees in Tenun Lurik MSMEs (Micro, Small, and Medium Enterprises) in the Special Region of Yogyakarta (DIY), both partially and simultaneously. The research employs a quantitative approach with a causal associative design. The research subjects consisted of all 101 employees of Tenun Lurik MSMEs in DIY, using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. Instrument validity was tested using Confirmatory Factor Analysis (CFA), and reliability was tested using Cronbach’s Alpha. The research findings reveal that: (1) Organizational commitment has a positive and significant effect on employee performance, with a regression coefficient (β) of 0.723 and a contribution (∆R²) of 40.5%; (2) Work ability has a positive and significant effect on performance, with a coefficient (β) of 0.732 and a contribution of 45.6%; (3) Work motivation also has a positive and significant effect on performance, with a coefficient (β) of 0.755 and a contribution of 45.5%; (4) Simultaneously, the three variables contribute 49.9% to employee performance, while the remaining 50.1% is influenced by other variables outside this study.